Validity and Reliability of Elementary School Students' Learning Motivation Instruments in Physical Education - Nur, Lutfi; Ginanjar, Agi; Malik, Arief Abdul; Pingon, Les (Universitas Suryakancana, 2021)
Motivation is one of the research variables that is widely studied in various scientific fields, including physical education and sports. However, at the elementary school level, there is still no motivational instrument in physical education that has good validity and reliability. This study aims to determine the validity and reliability of elementary students' learning motivation instruments in physical education. The research method uses descriptive research methods with a quantitative approach. The population used grade 4, 5, and 6 elementary school students in three different elementary schools in one sub-district in Indramayu district as many as 134 students with a sample of 50 taken using incidental sampling. The data collection technique used a learning motivation questionnaire. The data analysis technique used Cronbach's Alpha. The results of the study concluded that the elementary students' learning motivation instrument in physical education had very good reliability. In order to conduct further research with more complex analytical techniques in data analysis.Key words: validity, reliability, motivation, physical education